CYTOKINE LEVELS IN MATERNAL BLOOD AND UMBICAL CORD SERA FROM WOMEN WITH SYMPTOMS OF INTRAUTERINE INFECTION - I. A. Botvin’eva; L. V. Renge; V. N. Zorina; R. M. Zorina; A. N. Polukarov; L. G. Bazhenova (Медицинская иммунология, 2014)
Abstract. We had investigated serum levels of IL-6, IL-8, IL-10, IL-1ra and TNFα in peripheral blood of pregnant women at the terms of 38 to 40 weeks with polyhydramnios and serum IgG antibodies specific for Chlamydia trachomatis (titers of 1:20 to 1:40). Same parameters were tested in umbilical cord blood sera, obtained at delivery. We had found high levels of TNFα, IL-6, IL-8, IL-10 in sera from umbilical cord blood, and increased levels of TNFα in maternal sera before delivery in a group of women with high Apgar scores of their children (≥ 8 points), in comparison with control group. High levels of TNFα, IL-6, IL-10 in sera from umbical cord and increased serum concentrations of IL-6, IL-10, IL-1ra and TNFα before delivery were evaluated in group of women with circulating antibodies against C. trachomatis during pregnancy and with low degrees of newborn children (< 7 by Apgar score). We suggest that high cytokine levels in maternal blood and in sera of umbilical cord blood from women with polyhydramnios and circulating antibodies against C. trachomatis sufficiently correlate with high clinical risk of intrauterine infection in newborns. However, high inter-individual variability of the cytokine parameters does not permit their usage as independent diagnostic criteria.